Spotting talent in your team (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Have you ever had a new employee who looks perfect on paper but whose performance is poor when they start working? Thought so. You may also have experienced people who take on a new role or extra responsibility without a scrap of experience, yet perform exceptionally. What's the difference between those employees who fail and those who do extraordinarily well? According to Claudio Fernández-Aráoz, writing in the Harvard Business Review, the difference is potential - in other words, ""the ability to adapt to and grow into increasingly complex roles and environments."" In this track, we focus on why the potential of employees is vital to talent management, what the five main characteristics of potential are, and what you can do to ensure you discover the potential of job candidates at interviews. Before you hire your next person, listen to this course! Learning Objectives Learn to identify the importance a talent management strategy has in modern organisations Learn to discover how talent management strategies have begun to focus on 'potential' to address constantly shifting skill gaps Learn to uncover the 5 key elements of potential to look for in your team.